Axons in the Chick Embryo Follow Soft Pathways Through Developing Somite Segments - Julia Schaeffer; Julia Schaeffer; Isabell P. Weber; Amelia J. Thompson; Roger J. Keynes; Kristian Franze; Kristian Franze; Kristian Franze (Frontiers in Cell and Developmental Biology, 2022)
During patterning of the peripheral nervous system, motor axons grow sequentially out of the neural tube in a segmented fashion to ensure functional integration of the motor roots between the surrounding cartilage and bones of the developing vertebrae. This segmented outgrowth is regulated by the intrinsic properties of each segment (somite) adjacent to the neural tube, and in particular by chemical repulsive guidance cues expressed in the posterior half. Yet, knockout models for such repulsive cues still display initial segmentation of outgrowing motor axons, suggesting the existence of additional, yet unknown regulatory mechanisms of axon growth segmentation. As neuronal growth is not only regulated by chemical but also by mechanical signals, we here characterized the mechanical environment of outgrowing motor axons. Using atomic force microscopy-based indentation measurements on chick embryo somite strips, we identified stiffness gradients in each segment, which precedes motor axon growth. Axon growth was restricted to the anterior, softer tissue, which showed lower cell body densities than the repulsive stiffer posterior parts at later stages. As tissue stiffness is known to regulate axon growth during development, our results suggest that motor axons also respond to periodic stiffness gradients imposed by the intrinsic mechanical properties of somites.